A patrimonialização das Missões Jesuíticas em Misiones/AR e na região da Missões/BR - Mumbach, Sandi (2023)
The aim of this thesis is to understand the remnants heritage process of the Jesuitical Province of Paraguay presents in the territory of Misiones, Argentina. Comparisons with the heritage process occurred in Missões region in Rio Grande do Sul (RS), Brazil are made. During the 17th and 18th centuries, the Spanish missional project founded prosperous jesuit-indigenous settlements in La Plata River region. The dispute between the reigns of Portugal and Spain, in addition to South American national states formation process in the next century, caused the disintegration of those villages. Besides, the territory received a diverse population that migrated to it throughout the 19th and 20th centuries. Many buildings, however, have survived in the landscape and were integrated into the new society that started living there. Brazilian and Argentinian national historical heritage selection and protection policies encompassed those constructions over the 20th century. Political leaderships first activation intentions of the jesuitical-indigenous remnants were investigated by the research of law bills. Laws, decrees and bulletins were used to carefully analyze the performance of Argentinean Comisión Nacional de Monumentos Museos y Lugares Históricos. Then, the creation of the first provincial institutions to act over the historical heritage was enlightened. Hence, some aspects of the heritage process in Misiones and Missões-RS were raised to establish a comparative analysis: the general performance of Argentinean CNMMyLH and Brazilian SPHAN; their interventions over the sites of San Ignacio Mini and São Miguel Arcanjo, respectively; the valuation and heritage process of remnants undertaken by priests of the Society of Jesus in both regions. As a result, the work illuminates the heritage process in Misiones province, which is still not well explored by historiography. The found relations with the Brazilian process expands the vision over the Jesuit Missions heritage, which brings new elements to the topic. This thesis was a part of the research line Memória e Patrimônio from the Programa de Pós-Graduação em História of UFSM and was funded by CAPES/DS.